Production of the Documentary Film “The Second Body”: An Analysis of the Realities of Stunt Performers’ Lives in the Film Industry - Zainal Abidin Saputa; St. Tri Guntur Narwaya (Communigate, 2025)
The documentary film “The Second Body”: An Analysis of the Reality of Stuntmen’s Lives in the Film Industry is an audio-visual work that explores the everyday realities of stunt performers, namely professionals who confront high physical risks yet receive limited recognition and inadequate protection within the Indonesian film industry. Through an observational approach and in-depth interviews with active stuntmen, stunt coordinators, and action film directors, this documentary reveals a series of structural issues faced by stunt performers, including the absence of safety standards, lack of health insurance, financial inequality, and minimal appreciation for their contributions to cinematic productions. This research employs the theories of media representation and the social construction of reality to examine how stuntmen are portrayed in media and how their professional realities are shaped through social interactions within the film industry. The production process consisted of three main stages, namely pre-production, production, and post-production, each designed to present an authentic depiction of the physical risks, mental pressures, and dedication embodied by stunt performers. The documentary demonstrates that although stuntmen play a crucial role in creating dynamic and visually compelling action sequences, their position remains overshadowed by leading actors, a dynamic that reinforces the structural inequality embedded within the industry. The film aspires to serve as an advocacy medium, encouraging the film industry to implement proper safety standards, fair compensation schemes, and more meaningful recognition for the stunt profession.